A case of pulmonary actinomycosis presented with endobronchial involvement. (2019) - Oikonomidis, Petros; Fousekis, Fotios; Kotsaftis, Panagiotis; Pilios, Ioannis; Dimas, Dionysios; Giannoulis, Georgios
Abstract: Pulmonary actinomycosis is a rare infectious disease, which is characterized by a wide range of symptoms and no specific imaging findings and may be confused with neoplasia, tuberculosis or pneumonia. Endobronchial involvement of actinomycosis may be caused by aspiration of foreign bodies or broncholithiasis and may bronchoscopically masquerade as malignancy. A case of 68-year-old man is reported, who presented with productive cough and fever and had no response to antibiotic therapy with moxifloxacin. Patchy air-space consolidation on left lower lobe was demonstrated on CT and flexible bronchoscopy revealed an endobronchial white necrotized mass, causing partial occlusion of bronchus and masquerading as lung cancer. Endobronchial actinomycosis was confirmed by biopsies of lesion, which revealed radiating filamentous colonies of Actinomyces and no evidence of malignancy. The patient was successfully treated with intravenous penicillin G for two weeks, followed by doxycycline per oral for six months, achieving full resolution of lesion on follow-up CT and bronchoscopy and no recurrence of symptoms.